Development of the frequency PID tuning method with filter; Chemical Engineering Transactions; Vol. 52 - Kozin K. A. Kirill Andreevich; Egorova A. M. Anna Mikhaylovna; Mikhalevich S. S. Sergey Sergeevich; Manenti F. Flavio; Rossi F. Francesco (2016, 2016)
Title screen